Labor Turnover (LTO) Dalam Perspektif Ketenagakerjaan - Akhmad Junaedi (Jurnal Ketenagakerjaan, 2017)
Since the Orde Baru Government to date, employment developmnet changes very dynamically, which is characterized by the changes are quite striking among others related to the labor market, labor relations, working time and so on. In line with the era of free trade, regional collaborations such as Asean Economic Community, demanded a more flexible labor market in which workers/laborers are easier to move jobs through the labor relationship Employment Agreement Specific Time (PKWT)/Outsourcing. The working relationship through PKWT/Outsourcing, which is one form of embodiment of a flexible labor market, may encourage some workers/laborers out of work to get another job better, which is often called labor turnover (LTO). Laborturnover has consequences for workers, employers and national economy. Therefore, it becomes important to labor turnover is anticipated to be more restrained, which one of them through appropriate wage policy, the welfare of workers/laborers are adequate and consistent law enforcement.